Engaging First Peoples in Arts-Based Service Learning Towards Respectful and Mutually Beneficial Educational Practices - Bartleet, Brydie-Leigh; Bennett, Dawn; Power, Anne; Sunderland, Naomi (Landscapes: the Arts, Aesthetics, and Education, 2016)
This volume offers educators, higher education institutions, communities and organizations critical understandings and resources that can underpin respectful, reciprocal and transformative educative relationships with First Peoples internationally. With a focus on service learning, each chapter provides concrete examples of how arts-based, community-led projects can enhance and support the quality and sustainability of First Peoples' cultural content in higher education. In partnership with communities across Australia, Aotearoa New Zealand, Canada and the United States, contributors reflect on diverse projects and activities, offer rich and engaging first-hand accounts of student, community and staff experiences, share recommendations for arts-based service learning projects and outline future directions in the field.   All educators with an interest in enhancing future teachers' understanding of social justice and arts-based learning will benefit from reading this book. Arts-based service learning is here presented as a tool for stepping outside traditional classrooms, in order to learn about culture and to engage with real subjects. The central concepts reciprocity, meaningful service, reflection, development and diversity are discussed using a wide range of references to international research. Although many of the chapters concern Australian projects carried out with Australian first peoples communities and Australian universities, the editors present the challenges and affordances on an analytical and reflective level that is both inspiring and useful to international readers. Eva Saether, Lund University, Sweden.